Agricultural impacts of climate change / handbook of conservation agriculture - Kumar, Rohitashw,ed. (Boca Raton CRC Press, 2020)
"Conservation agriculture is a sustainable production model that not only optimizes crop yields, but also reaps economic and environmental benefits as well. The adoption of successful conservation agriculture methods has resulted in energy savings, higher organic matter content and biotic activity in soil, increased crop-water availability and thus resilience to drought, improved recharge of aquifers, less erosion, and reduced impacts from the weather associated with climate change in general. Agricultural Impacts of Climate Change examines several important aspects of crop production, such as climate change, soil management, farm machinery, and different methods for sustainable conservation agriculture. It presents spatial distribution of a daily, monthly and annual precipitation concentration indices, Diffuse Reflectance Fourier Transform Infrared Spectroscopy for analyzing the organic matter in soil, and adaptation strategies for climate-related plant disease scenarios. It also discusses solar energy-based greenhouse modeling, precision farming using remote sensing and GIS, and various types of machinery used for conservation agriculture. Features: Examines the effects of climate change on agriculture and the related strategies for mitigation through practical, real-world examples Explores innovative on-farm technology options to increase system efficiency resulting in improved water usage Presents examples of precision farming using climate-resilient technologies"--
Includes bibliographical references and index.
Keywords: Crops and climate; Agriculture; Sustainable agriculture; Climate change mitigation; Crop yields